2009
DOI: 10.1088/1674-4926/30/7/074004
|View full text |Cite
|
Sign up to set email alerts
|

A low-loss V-groove coplanar waveguide on an SOI substrate

Abstract: A novel low-loss 50-Ω coplanar waveguide with V-groove on an SOI substrate is proposed. Through a CMOS-compatible process and anisotropic etching of silicon, surface silicon is removed from the SOI. The measured results show that the V-groove coplanar waveguide causes about 50% less loss than the conventional one at a high frequency of up to 40 GHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…They observe that the insertion losses can be reduced from >2 dB mm -1 to ~1 dB mm -1 . The findings here suggest that the reduced losses observed by Yuhang et al [44] have, at least in part, their origin at interfaces between the tracks. Finally, in terms of losses associated with a buried layer, Neve et al [45] showed that a buried trap-rich layer could reduce losses of CPW on silicon having a resistivity in the range 2-5 kΩ cm.…”
Section: Comparisons Of Results With Measurements On Comparable Cpwsupporting
confidence: 64%
See 1 more Smart Citation
“…They observe that the insertion losses can be reduced from >2 dB mm -1 to ~1 dB mm -1 . The findings here suggest that the reduced losses observed by Yuhang et al [44] have, at least in part, their origin at interfaces between the tracks. Finally, in terms of losses associated with a buried layer, Neve et al [45] showed that a buried trap-rich layer could reduce losses of CPW on silicon having a resistivity in the range 2-5 kΩ cm.…”
Section: Comparisons Of Results With Measurements On Comparable Cpwsupporting
confidence: 64%
“…They found that CPW on a thermal oxide (SiO 2 ) on high-resistivity (>5000 Ω cm) silicon was more sensitive to DC biasing and its polarity than MS-implying that buried interface charges (and their absorption) underneath tracks were at the origin of a significant proportion of the losses in this system. Yuhang et al [45] proposed lower-loss a 'V-groove' CPW based on SOI wafers. Using CPW having a signal-to-ground gap width of 30 µm.…”
Section: Comparisons Of Results With Measurements On Comparable Cpwmentioning
confidence: 99%